To live as long as heaven and earth : a translation and study of Ge Hong's traditions of divine transcendents - Campany, Robert Ford, 1959-; Ge, Hong, 284-364. (Berkeley : University of California Press, 2002)
In late classical and early medieval China, ascetics strove to become transcendents--deathless beings with supernormal powers. Practitioners developed dietetic, alchemical, meditative, gymnastic, sexual, and medicinal disciplines (some of which are still practiced today) to perfect themselves and thus transcend death. Narratives of their achievements circulated widely. Ge Hong (283-343 c.e.) collected and preserved many of their stories in his Traditions of Divine Transcendents, affording us a window onto this extraordinary response to human mortality. Robert Ford Campany's groundbreaking and carefully researched text offers the first complete, critical translation and commentary for this important Chinese religious work, at the same time establishing a method for reconstructing lost texts from medieval China. Clear, exacting, and annotated, the translation comprises over a hundred lively, engaging narratives of individuals deemed to have fought death and won. Additionally, To Live as Long as Heaven and Earth systematically introduces the Chinese quest for transcendence, illuminating a poorly understood tradition that was an important source of Daoist religion and a major social, cultural, and religious phenomenon in its own right.
ILLUSTRATIONS; FOREWORD; PREFACE; ACKNOWLEDGMENTS; Opening; Ge Hong and the Writing of Traditions of Divine Transcendents; Traditions as Hagiography; Text-Critical Matters; Conventions; Group A: Earliest-Attested Fragments; Group B: Early-Attested Hagiographies; Group B: Early-Attested Fragments; Group C: Later-Attested Hagiographies; On the Source Texts and the Temporal Differentiation of Passages; Items Attributed to Shenxian zhuan Excluded from This Translation; BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 553-579) and index.
Print version record.
JSTOR
Keywords: Ge, Hong, -- 284-364.; Shen xian zhuan (Ge, Hong); Taoists -- China -- Biography; Taoïstes -- Chine -- Biographies; RELIGION -- Taoism; Taoists; China; Filosofie; Biography; Biographies; Biographies; Biographies